RESIDENTIAL SERVICES AS A MAJOR COST DRIVER IN MENTAL HEALTH AND SUBSTANCE USE SERVICES IN SOUTHERN FINLAND - Minna Sadeniemi, MD; Grigori Joffe, Professor, MD, PhD; Sami Pirkola, Professor, MD, PhD; Taina Ala-Nikkola, MSci, PhD; Raija Kontio, MSci, PhD; Kristian Wahlbeck, Professor, MD, PhD (Psychiatria Fennica, 2021)
Mental health and substance abuse services (MHS) have gone through major changes throughout Western countries. In searching for best practices, there is a need for benchmarking data on ways to allocate resources and organize services. In Finland, the closing of psychiatric hospitals during the last 50 years has partly led to transinstitutionalization to non-hospital residential services. We set out to study the provision of beds and personnel resources in non-hospital residential services in southern Finland, and whether the residential services’ personnel resources and primary care orientation of services predict the total personnel costs of the MHS. We mapped the MHS with the European Service Mapping Schedule – Revised (ESMS-R). For the statistical analysis, we used the Spearman correlation and linear regression models. There were 333 non-hospital residential service beds per 100,000 adults and 119.5 full-time equivalent (FTE) personnel per 100,000 adults in the nonhospital residential services. The personnel resources in the hospital and non-hospital residential services were both significant predictors of total personnel costs. The association between non-hospital personnel and total personnel costs was not explained by sociodemographic indicators of the need for services. Of the personnel in the non-hospital residential services, 0.8% were physicians, 16.8% were nurses, 0.1% were psychologists, 0.6% were social workers and 82% were other professionals (mostly auxiliary nurses). Non-hospital residential services are a significant part of the MHS in Finland, and special attention should be paid to the coordination and the quality of care in these institutions.